Parametric Analysis of Variable Stator Vane System in Gas Turbines Based on Cosimulation of its Refined Model and System Dynamic Performance Model. Issue 12 (17th October 2021) - Jia, Xingyun; Zhou, Dengji; Huang, Dawen; Xiao, Wang; Xu, Luyao; Hao, Jiarui
Abstract: The variable stator vane (VSV) system is a key component of gas turbine supercharged rotor components for anti‐surge, and its performance directly affects the working stability and economy of the gas turbine. The effect of the VSV system on the dynamic characteristics and control performance of the gas turbine cannot be known. Then a refined model of the VSV system refined to design parameters established and studied to explore the effect of gas turbine dynamic performance based on co‐simulation. The effects of key parameters on the performance of the gas turbine system are analyzed by embedding the refined VSV model into the engine model. The simulation results prove that servo amplifier gain, viscous friction coefficient and dead band are sensitive structural parameters that affect the dynamic performance of the gas turbines. In the proposed appropriate interval, the optimal sensitive parameters can reduce the overshoot and adjustment time by about 51% and 7%. The gain of the servo amplifier is positively correlated with the maximum opening of the VSV. When the dynamic performance of the control system has been exerted to its extreme, some nonlinear parameters of the actuator can greatly improve the overall performance of the complex system. Abstract : A refined variable stator vane (VSV) system model coupling with the multi‐objective closed‐loop control system of the dynamic gas turbine whole machine model is proposed to study the effect and interrelated mechanism of several key parameters of VSV on the dynamic performance of the gas turbine system, including servo amplifier gain, viscous friction coefficient, and dead band.